Porous metal material and preparation method thereof

By mixing metal powder and other materials in proportion, tape-casting and rolling, and then sintering, the problems of complex preparation methods, serious pollution and low yield of traditional porous metal materials are solved, and high-efficiency manufacturing methods suitable for a variety of metal materials are realized. Preparation, with good shielding properties.

CN119346862APending Publication Date: 2025-01-24SUZHOU TIANMAI THERMAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411479731.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The traditional preparation method of porous metal materials has problems such as complex process, serious pollution, and can only be applied to individual metal materials and has a very low yield.

Method used

After mixing the metal powder, adhesive, pores, thickeners, and water in a certain percentage, the flow was imported for a streaming scroll, and sintering treatment was finally performed to prepare porous metal materials.

Benefits of technology

This method can prepare porous metal materials with good shielding performance, suitable for a variety of metal materials, and can improve production efficiency and reduce the generation of waste gas and wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346862A_ABST
    Figure CN119346862A_ABST
Patent Text Reader

Abstract

The invention discloses a porous metal material and a preparation method thereof.The preparation method comprises the steps that metal powder, a binding agent, a pore forming agent, a thickening agent and water are mixed and stirred according to a certain proportion, and tape casting slurry is obtained; the tape casting slurry is guided into a tape casting machine to be subjected to tape casting and rolling, and a metal composite film is obtained; and the metal composite film is sintered and cooled in sequence, and the porous metal material is obtained. According to the preparation method, the problems that a traditional porous method is complex in process, serious in pollution, only suitable for individual metal materials and low in yield are solved, and the porous metal material with the good shielding performance is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a porous metal material and a preparation method thereof. Background Art

[0002] Porous metal materials refer to metals with a large number of directional or random holes distributed inside. According to the type of holes, they can be divided into open-cell and closed-cell types. They are a new type of engineering materials and functional materials with good physical properties and good mechanical properties. Porous metal materials are widely used in aerospace, transportation, construction engineering, mechanical engineering, electrochemical engineering and environmental protection engineering due to their unique structure and properties. These application fields have specific requirements for the performance of materials. Porous metal materials can meet these requirements well due to their light weight, high specific surface area, good vibration and sound absorption properties and other characteristics.

[0003] Traditional methods for preparing porous metal materials generally use template method and melt foaming method.

[0004] The template method refers to a method of using a porous template in combination with a metal material to form a pore structure in the metal material. In the production process, a suitable porous template is first selected, such as particles, fibers, membranes, foams, etc.; then the porous template is used in combination with the metal material to obtain a composite material, such as a sol-gel method, an electrochemical deposition method, a vapor deposition method, etc.; finally, the prepared composite material is subjected to heat treatment, such as roasting, annealing, etc., to remove the porous template and obtain a porous metal material. However, the template method has problems such as complex process and serious pollution.

[0005] The melt foaming method refers to first adding a foaming agent to the metal for melting, and then insulating and foaming it. Since aluminum has a low melting point, it does not require special protective gas and is easy to produce, so the melt foaming method is often used for porous aluminum materials. However, the melt foaming method has limitations and can only be applied to individual metal materials. For metals with high melting points such as copper, nickel, and titanium, the yield of the corresponding porous metal materials is very low, making it difficult to use this method.

[0006] Moreover, the traditional method of preparing porous metal materials not only has low production efficiency, but also generates a lot of waste gas and wastewater during the production process, and consumes a lot of energy.

[0007] The present invention solves at least one of the above problems. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a porous metal material, which is used to solve the problems of complex process, serious pollution, and only being applicable to individual metal materials and having a very low yield rate in traditional porous methods. The porous metal material prepared in this application has good shielding properties.

[0009] The purpose of the present invention is achieved by the following technical solutions:

[0010] A first aspect of the present invention provides a method for preparing a porous metal material, comprising:

[0011] The metal powder, the binder, the pore-forming agent, the thickener and the water are mixed and stirred in a certain proportion to obtain a casting slurry;

[0012] The casting slurry is introduced into a casting machine for casting and winding to obtain a metal composite film;

[0013] The metal composite membrane is sintered in sequence to obtain a porous metal material.

[0014] In some possible embodiments, in the process of obtaining the casting slurry, the content of the metal powder is 20wt% to 70wt%, the content of the binder is 5wt% to 20wt%, the content of the pore-forming agent is 5wt% to 20wt%, the content of the thickener is 0.1wt% to 2wt%, and the content of water is 10wt% to 40wt%.

[0015] In some possible implementations, the metal powder includes at least one or more of nickel powder, stainless steel powder, aluminum powder, copper powder, titanium powder and silver powder.

[0016] In some possible implementations, the binder includes at least one or more of waterborne polyurethane, waterborne epoxy resin, waterborne acrylic resin, waterborne silicone resin, waterborne acrylamide and polyvinyl alcohol.

[0017] In some possible implementations, the pore-forming agent includes at least one or more of carbon powder, ammonium bicarbonate, ammonium carbonate, urea, azodicarbonamide, azobisisobutyronitrile, 4,4-oxybisbenzenesulfonylhydrazide, p-toluenesulfonylhydrazide, spherical PS and spherical PMMA.

[0018] In some possible implementations, the thickener includes at least one or more of lithium magnesium silicate, magnesium aluminum silicate, fumed SiO2, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

[0019] In some possible implementations, during the process of the casting machine performing casting and winding, the gap of the casting die head of the casting machine is 0.2-20 mm; the drying tunnel temperature of the casting machine is 40-100° C., which is set in a gradient sequence; the casting blast of the casting machine is 100-300 m 3 / h, the casting speed of the casting machine is 0.1m~1m / min, the casting base belt of the casting machine is a PET film, and the thickness of the PET film is 70~300um; the winding tension and unwinding tension of the casting machine are 100~600N respectively.

[0020] In some possible implementations, the drying tunnel temperature increases first and then decreases.

[0021] In some possible implementations, the sintering process includes a first sintering process and a second sintering process performed sequentially, wherein the first sintering process includes: sintering in an air environment at a temperature of 300 to 500° C. for 1 to 24 hours;

[0022] The second sintering treatment includes: sintering in a vacuum or argon or nitrogen or nitrogen-hydrogen mixed gas environment at a temperature of 600-1200° C. for 1-24 hours.

[0023] A second aspect of the present invention provides a porous metal material prepared by the above-mentioned preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic diagram of the scanning electron microscope structure of the porous nickel material of Example 1 of the present invention;

[0025] Figure 2 Schematic diagram of the scanning electron microscope structure of the porous copper material of Example 2 of the present invention. DETAILED DESCRIPTION

[0026] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make the present invention more comprehensive and complete and to fully convey the concepts of example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.

[0027] This embodiment provides a method for preparing a porous metal material, comprising:

[0028] Step S1: Mix and stir metal powder, binder, pore-forming agent, thickener and water in a certain proportion to obtain a casting slurry.

[0029] In this embodiment, the metal powder may be one or more of nickel powder, stainless steel powder, aluminum powder, copper powder, titanium powder or silver powder.

[0030] Furthermore, the metal powder is irregular or spherical.

[0031] Spherical metal powder has obvious advantages over irregular metal powder in the preparation of porous materials. First, spherical metal powder has the advantages of high sphericity, smooth surface, high purity, low oxygen content, small particle size and uniform distribution. These characteristics make spherical metal powder have excellent fluidity, dispersibility and packing density. Therefore, porous metal materials prepared using spherical metal powder have better machinability.

[0032] Furthermore, when the metal powder is nickel powder, the nickel content is ≥99.5%, the mesh number is 50-1000mesh, and the bulk density is 2-5g / cm 3 In this embodiment, the mesh size of the nickel powder can be 50 mesh, 300 mesh, or 10000 mesh, preferably 300 mesh; the bulk density can be 2 g / cm 3 , 3.5g / cm 3 , 5g / cm 3 Nickel powder of this specification has good formability and can flow and fill better during the preparation of porous metal materials, thereby improving the density and uniformity of porous metal materials.

[0033] When the metal powder is copper powder, the copper content is ≥99.5, the mesh number is 50-1000mesh, and the bulk density is 2-4g / cm 3 In this embodiment, the mesh size of the copper powder can be 50 mesh, 180 mesh, or 1000 mesh, preferably 180 mesh, and the bulk density can be 2 g / cm 3 , 3g / cm 3 , 4g / cm 3 Copper powder of this specification can effectively avoid the agglomeration phenomenon of porous metal materials during the preparation process, eliminate coarse and uneven organizational structure, and thus improve the overall performance of porous metal materials.

[0034] When the metal powder is stainless steel powder, the mesh number is 100-800mesh, and the bulk density is 2-4g / cm 3 In this embodiment, the mesh size of the stainless steel powder can be 100 mesh, 300 mesh, or 800 mesh, preferably 300 mesh; the bulk density can be 2 g / cm 3 、3.2g / cm 3 , 4g / cm 3 Stainless steel powder under this specification can not only ensure good fluidity and formability, but also meet the basic strength requirements of porous metal materials.

[0035] When the metal powder is silver powder, the silver content is >99%, the mesh size is 500-1500mesh, and the bulk density is 1-3g / cm 3In this embodiment, the mesh size of the silver powder can be 500 mesh, 800 mesh, or 1500 mesh, preferably 800 mesh; the bulk density can be 1 g / cm 3 , 2g / cm 3 , 3g / cm 3 Silver powder of this specification can provide a high specific surface area while ensuring fluidity, thereby enhancing the material's adsorption capacity, catalytic activity and other surface-related physical and chemical properties, meeting the material's various application requirements.

[0036] When the metal powder is aluminum powder, the aluminum content is ≥99.5%, the mesh number is 100-800mesh, and the bulk density is 0.8-1.3g / cm 3 Moderate bulk density helps to improve the fluidity of the powder, making it easier to achieve automated control in the production process of porous metal materials, further improving production efficiency and consistency of product quality.

[0037] When the metal powder is titanium powder, the mesh number is 300-3000 mesh, the titanium content is >99%, and the bulk density is 2-3 g / cm 3 Titanium powder of this specification can ensure the formation of a more uniform porous structure during the sintering process, further improving product quality.

[0038] In some specific embodiments, in the process of obtaining the casting slurry, the content of metal powder is 20wt% to 70wt%, the content of binder is 5wt% to 20wt%, the content of pore-forming agent is 5wt% to 20wt%, the content of thickener is 0.1wt% to 2wt%, and the content of water is 10wt% to 40wt%.

[0039] The binder includes at least one or more of waterborne polyurethane, waterborne epoxy resin, waterborne acrylic resin, waterborne silicone resin, waterborne acrylamide and polyvinyl alcohol. The above binders use water as a solvent, and while playing their respective roles in the reaction system of the casting slurry, they also have good environmental performance.

[0040] As a polymer material, waterborne polyurethane can significantly improve the strength and toughness of porous metal materials when combined with metal powder.

[0041] Waterborne polyurethane has the advantages of no pollution, safety and reliability, excellent mechanical properties, good compatibility, and easy modification. These characteristics make waterborne polyurethane easy to process and modify in the process of preparing porous metal materials.

[0042] In contrast, oily polyurethane releases toxic and harmful organic solvents and odors, while water-based polyurethane uses water as a solvent. It has good environmental performance in the preparation process of porous metal materials and avoids the environmental pollution and health risks that may be caused by the use of organic solvents.

[0043] In this embodiment, when the metal powder is nickel powder, the binder may preferably be water-based polyurethane.

[0044] Water-based acrylic resin uses water as solvent. Compared with traditional organic solvent-based resins, its preparation and application process greatly reduces the emission of volatile organic compounds and is more environmentally friendly to the preparation of porous metal materials.

[0045] In this embodiment, when the metal powder is copper powder, the binder may preferably be water-based acrylic resin.

[0046] Water-based silicone resin is an environmentally friendly and non-toxic material that does not cause harm to the human body or the environment. When preparing porous metal materials from metal powder, the use of water-based silicone resin can ensure the safety and environmental friendliness of the final product.

[0047] In this embodiment, when the metal powder is stainless steel powder, the binder may preferably be a water-based silicone resin.

[0048] Polyvinyl alcohol (PVA), as a nonionic surfactant, can play an important role in dispersion and bonding in the process of preparing porous metal materials from metal powder. By using polyvinyl alcohol as a binder, a more uniform porous metal material can be obtained.

[0049] In this embodiment, when the metal powder is silver powder, the binder may preferably be polyvinyl alcohol.

[0050] The pore-forming agent includes at least one or more of carbon powder, ammonium bicarbonate, ammonium carbonate, urea, azodicarbonamide, azobisisobutyronitrile, 4,4-oxybisbenzenesulfonylhydrazide, p-toluenesulfonylhydrazide, spherical PS and spherical PMMA.

[0051] Spherical PS (polystyrene) is used as a template or filler to occupy a place in the preparation process of porous metal materials. After casting and sintering, a predetermined porous structure is formed.

[0052] In this embodiment, when the metal powder is nickel powder, the pore-forming agent may preferably be spherical PS.

[0053] Urea can be decomposed at a relatively high temperature, so the applicant has found that it can be an ideal pore-forming agent for preparing porous metal materials. After being mixed with metal powder, urea will decompose during heating to produce gas, thereby forming pores in the metal matrix, thereby obtaining a porous metal material.

[0054] In addition, the gas products produced by the decomposition of urea have less pollution to the porous metal material, and the decomposition of urea at a relatively low temperature can avoid the reaction between the urea decomposition products and the porous metal material.

[0055] In this embodiment, when the metal powder is copper powder, the pore-forming agent may preferably be urea.

[0056] The principle of spherical PMMA (polymethyl methacrylate) and spherical PS as pore-forming agents is the same, and the target pore size is obtained by occupying the position.

[0057] In this embodiment, when the metal powder is silver powder, the pore-forming agent may preferably be spherical PMMA.

[0058] Azobisisobutyronitrile (AIBN) can promote the polymerization and foaming of high molecular polymers. By controlling the gas produced by its decomposition, a microporous structure can be formed in the metal powder composite material. This microporous structure increases the surface area of ​​the material. In addition, nitrogen, the decomposition product of AIBN, is a harmless gas that helps to form a uniform and stable microporous structure.

[0059] In this embodiment, when the metal powder is stainless steel powder, the pore-forming agent may preferably be azobisisobutyronitrile.

[0060] The thickener includes at least one or more of lithium magnesium silicate, magnesium aluminum silicate, fumed SiO2, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

[0061] Hydroxymethyl cellulose helps to control the viscosity and stability of the suspension during the preparation process, thereby ensuring the uniform dispersion of the metal powder particles in the solvent and providing a basis for the subsequent formation of a porous structure.

[0062] In this embodiment, when the metal powder is nickel powder, the thickener may preferably be hydroxymethyl cellulose.

[0063] In the process of preparing porous metal materials, hydroxyethyl cellulose can help adjust the viscosity of the material, thereby controlling the fluidity and stability of the casting slurry. This is particularly important for the preparation of porous metal materials, because the appropriate viscosity can affect the structure and performance of porous metal materials.

[0064] In addition, hydroxyethyl cellulose also has the function of protecting moisture, which is also very important for maintaining the wettability and stability of porous metal materials. In the preparation process of porous metal materials, hydroxyethyl cellulose can not only increase the viscosity of the material, but also help fix and strengthen the structure of the material through its film-forming and adhesive properties.

[0065] In this embodiment, when the metal powder is copper powder or silver powder, the thickener may preferably be hydroxyethyl cellulose.

[0066] In the preparation process of porous metal materials, polyamide wax can effectively prevent the sedimentation of metal powder particles and maintain their uniformity in the tape casting slurry. In addition, polyamide wax can also form a three-dimensional network structure in the entire tape casting slurry system through intermolecular hydrogen bonds. This structure fixes and supports the metal powder particles, thereby effectively preventing the metal powder particles from settling and improving the processing performance of the material.

[0067] In this embodiment, when the metal powder is stainless steel powder, the thickener may preferably be polyamide wax.

[0068] Step S2: introducing the casting slurry into a casting machine for casting and winding to obtain a metal composite film.

[0069] As an example, during the process of film casting and winding, the gap of the film casting die head of the film casting machine is 0.2-20 mm; the drying tunnel temperature of the film casting machine is 40-100°C, which is set in a gradient sequence; the film casting blast of the film casting machine is 100-300m 3 / h, the casting speed of the casting machine is 0.1m~1m / min, the casting base belt of the casting machine is PET film, and the thickness of the PET film is 70~300um; the winding tension and unwinding tension of the casting machine are 100~600N respectively.

[0070] It should be further explained that the temperature of the drying tunnel is set in a gradient in sequence, which means that the temperature of each section in the drying tunnel is set in sequence. In this embodiment, the drying tunnel is preferably six sections.

[0071] Step S3: Sintering the metal composite film to obtain a porous metal material.

[0072] It should be noted that the sintering treatment includes a first sintering treatment and a second sintering treatment. The first sintering treatment includes: sintering in an air environment at a temperature of 300 to 500° C. for 1 to 24 hours to debond the polymer material in the metal composite film.

[0073] The second sintering treatment includes: sintering for 1 to 24 hours in a vacuum or argon or nitrogen or nitrogen-hydrogen mixed gas environment at a temperature of 600 to 1200° C., so as to sinter the metals in the metal composite film together to form a porous metal material.

[0074] It should be further explained that the sintering atmosphere and sintering temperature of different metal materials are different. Polymer materials can usually be completely debonded at 300-500°C. If the temperature of the first sintering treatment is higher than the temperature of the second sintering treatment, the metal may react with the substances produced by the decomposition of the polymer. Even if there is no reaction, energy consumption will increase.

[0075] A second aspect of the present invention provides a porous metal material prepared by the above-mentioned preparation method.

[0076] The technical solution of the present application will be described in more detail below, but it should be understood that the following examples are only for explaining and illustrating the technical solution, but do not limit the scope of the present application. Moreover, unless otherwise specified, the various raw materials, reaction equipment, detection equipment and methods used in the following examples are all known in the art.

[0077] Example 1

[0078] A method for preparing a porous nickel material comprises steps S1 to S3.

[0079] Step S1: Mix and stir metal powder, binder, pore-forming agent, thickener and water in a certain proportion to obtain a casting slurry.

[0080] Specifically, 2 kg of waterborne polyurethane was first added to 2 kg of water, and then added into the reactor together with 20 g of hydroxymethyl cellulose and 300 g of spherical PS with a particle size of 100 μm, and stirred at the first frequency (30 Hz) for 1 h at room temperature. 3 4 kg of atomized nickel powder was put into the reactor, and stirring was continued at the second frequency (30 Hz) for 1 hour, and then vacuum was evacuated and stirring was continued for 2 hours to obtain a casting slurry for use.

[0081] Step S2: introducing the casting slurry into a casting machine for casting and winding to obtain a metal composite film.

[0082] Specifically, the gap of the casting die of the casting machine is adjusted to 1mm; the drying channel temperature of the casting machine is adjusted to 40℃, 60℃, 80℃, 80℃, 60℃, 40℃ in a gradient sequence. The casting blast size of the casting machine is adjusted to 100m 3 / h; adjust the casting speed of the casting machine to 0.2m / min, select a PET film with a thickness of 70um for the casting base band of the casting machine, adjust the winding tension and unwinding tension of the casting machine to 500N respectively, and then introduce the casting slurry into the casting die head position of the casting machine, and the casting is dried and rolled to obtain a polyurethane-nickel composite film with a thickness of 0.25mm.

[0083] Step S3: sintering and cooling the metal composite film in sequence to obtain a porous metal material.

[0084] Specifically, the polyurethane-nickel composite film is cut into a size of 300mm*150mm, and then sent to two continuous kilns in sequence for the first sintering treatment and the second sintering treatment. The first sintering treatment includes: sintering and degumming for 6 hours in an air environment at a temperature of 500°C in the first continuous kiln, and then performing the second sintering treatment. The second sintering treatment includes: sintering for 12 hours in a nitrogen-hydrogen mixed gas (15% hydrogen) environment at a temperature of 1000°C in the second continuous kiln; finally, cooling and taking out of the kiln to obtain a porous nickel material.

[0085] After testing, the thickness of the porous nickel material is 0.25mm; the density is 2.5g / cm3; the average pore size is 30um; the porosity is 70%; and the gas permeability is 8.0um 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.1 to 0.6; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 80 to 110dB.

[0086] Example 2

[0087] A method for preparing a porous copper material comprises steps S1 to S3.

[0088] Step S1: Mix and stir metal powder, binder, pore-forming agent, thickener and water in a certain proportion to obtain a casting slurry.

[0089] Specifically, 1 kg of water-based acrylic resin was first added to 3 kg of water, and then added into a reactor together with 20 g of hydroxyethyl cellulose and 30 g of urea, and stirred at room temperature at a first frequency (30 Hz) for 1 h. 3 2.5 kg of atomized copper powder was put into the reactor, and stirring was continued at the second frequency (50 Hz) for 1 hour, and then vacuum was evacuated and stirring was continued for 3 hours to obtain a casting slurry for use.

[0090] Step S2: introducing the casting slurry into a casting machine for casting and winding to obtain a metal composite film.

[0091] Specifically, the gap of the casting die of the casting machine is adjusted to 1 mm; the drying channel temperature of the casting machine is adjusted to 40°C, 60°C, 80°C, 80°C, 60°C, and 40°C in a gradient sequence; the casting blast size of the casting machine is adjusted to 200m 3 / h; adjust the casting speed of the casting machine to 0.1m / min, select a PET film with a thickness of 100um for the casting base band of the casting machine, adjust the winding tension and unwinding tension of the casting machine to 500N respectively, and then introduce the casting slurry into the casting die head position of the casting machine, and the casting is dried and rolled to obtain an acrylic-copper composite film with a thickness of 0.5mm.

[0092] Step S3: sintering and cooling the metal composite film in sequence to obtain a porous metal material.

[0093] Specifically, the polyurethane-nickel composite film is cut into a size of 300mm*150mm, and then sent to two continuous kilns in sequence for the first sintering treatment and the second sintering treatment. The first sintering treatment includes: sintering and degumming for 6 hours in an air environment at a temperature of 500°C in the first continuous kiln, and then performing the second sintering treatment. The second sintering treatment includes: sintering for 12 hours in a nitrogen-hydrogen mixed gas (15% hydrogen) environment at a temperature of 950°C in the second continuous kiln; finally, cooling and taking out of the kiln to obtain a porous copper material.

[0094] After testing, the thickness of the porous copper material is 0.5mm; the density is 2.7g / cm3; the average pore size is 20um; the porosity is 75%; and the gas permeability is 6.0um 2 ; In the frequency range of 1 to 4K Hz, the sound absorption coefficient is 0.2 to 0.8; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 70 to 100dB.

[0095] Example 3

[0096] A method for preparing a porous stainless steel material comprises steps S1 to S3.

[0097] Step S1: Mix and stir metal powder, binder, pore-forming agent, thickener and water in a certain proportion to obtain a casting slurry.

[0098] Specifically, 2 kg of water-based silicone resin was added to 1 kg of water, and then put into a reactor with 200 g of polyamide wax and 20 g of azobisisobutyronitrile, and stirred at room temperature at a first frequency (30 Hz) for 1 h. 3 1.5 kg of 316L stainless steel powder was put into the reactor, stirred at the second frequency (50 Hz) for 1 hour, and then vacuumed and stirred for 2 hours to obtain a casting slurry for use.

[0099] Step S2: introducing the casting slurry into a casting machine for casting and winding to obtain a metal composite film.

[0100] Specifically, the gap of the casting die of the casting machine is adjusted to 0.5 mm; the drying channel temperature of the casting machine is adjusted to 40°C, 60°C, 80°C, 80°C, 60°C, and 40°C in a gradient sequence; the casting blast size of the casting machine is adjusted to 100m 3 / h; adjust the casting speed of the casting machine to 0.3m / min, select a PET film with a thickness of 100um for the casting base band of the casting machine, adjust the winding tension and unwinding tension of the casting machine to 500N respectively, and then introduce the casting slurry into the casting die head position of the casting machine, and the casting is dried and rolled to obtain a silicone-stainless steel composite film with a thickness of 0.1mm.

[0101] Step S3: sintering and cooling the metal composite film in sequence to obtain a porous metal material.

[0102] Specifically, the organosilicon-stainless steel composite film is cut into a size of 300mm*150mm, and then sent to two-stage continuous kilns in sequence for the first sintering treatment and the second sintering treatment. The first sintering treatment includes: sintering and degumming for 6 hours in an air environment at a temperature of 400°C in the first continuous kiln, and then performing the second sintering treatment. The second sintering treatment includes: sintering for 2 hours in a vacuum environment at a temperature of 1000°C in the second continuous kiln; finally, cooling and taking out of the kiln to obtain the porous stainless steel material.

[0103] After testing, the thickness of the porous stainless steel material is 0.1mm; the density is 1.5g / cm3; the average pore size is 15um; the porosity is 75%; and the gas permeability is 3.0um 2 ; In the frequency range of 1 to 4K Hz, the sound absorption coefficient is 0.1 to 0.3; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 40 to 80dB.

[0104] Example 4

[0105] A method for preparing a porous stainless steel material comprises steps S1 to S3.

[0106] Step S1: Mix and stir metal powder, binder, pore-forming agent, thickener and water in a certain proportion to obtain a casting slurry.

[0107] Specifically, 300 g of polyvinyl alcohol was added to 3 kg of water, and then dissolved at a temperature of 95 ° C and a stirring frequency of 20 Hz for 2 hours, and cooled to room temperature; then, 300 g of hydroxyethyl cellulose and 200 g of spherical PMMA with a particle size of 10 μm were put into a reactor, stirred at a first frequency (30 Hz) for 1 hour at room temperature, and then a mesh number of 800 mesh and a bulk density of 1 g / cm 3 1 kg of silver powder was put into the reactor, stirred at the second frequency (50 Hz) for 1 hour, and then vacuumed and stirred for 2 hours to obtain a casting slurry for use.

[0108] Step S2: introducing the casting slurry into a casting machine for casting and winding to obtain a metal composite film.

[0109] Specifically, the gap of the casting die of the casting machine is adjusted to 0.2 mm; the drying channel temperature of the casting machine is adjusted to 40°C, 60°C, 70°C, 70°C, 60°C, and 50°C in a gradient manner; the casting blast size of the casting machine is adjusted to 100m 3 / h; adjust the casting speed of the casting machine to 0.3m / min, select a PET film with a thickness of 100um for the casting base band of the casting machine, adjust the winding tension and unwinding tension of the casting machine to 500N respectively, and then introduce the casting slurry into the casting die head position of the casting machine, and the casting is dried and rolled to obtain a polyvinyl alcohol-silver composite film with a thickness of 0.05mm.

[0110] Step S3: sintering and cooling the metal composite film in sequence to obtain a porous metal material.

[0111] Specifically, the polyvinyl alcohol-silver composite film is cut into a size of 300mm*150mm, and then sent to two continuous kilns in sequence for the first sintering treatment and the second sintering treatment. The first sintering treatment includes: sintering and degumming for 6 hours in an air environment at a temperature of 400°C in the first continuous kiln, and then performing the second sintering treatment. The second sintering treatment includes: sintering for 1 hour in a vacuum environment at a temperature of 800°C in the second continuous kiln; finally, cooling and taking out of the kiln to obtain the porous silver material.

[0112] After testing, the thickness of the porous silver material is 0.05mm; the density is 3.5g / cm3; the average pore size is 12um; the porosity is 60%; and the gas permeability is 1.0um 2 ; In the frequency range of 1 to 4K Hz, the sound absorption coefficient is 0.1 to 0.3; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 70 to 100dB.

[0113] Example 5

[0114] The difference from Example 1 is that the bulk density of nickel powder is 3.5 g / cm 3 .

[0115] It can be seen from Examples 1 and 5 that as the bulk density of nickel powder increases, the average pore size decreases to 25 μm, the porosity decreases to 60%, and the gas permeability decreases to 6.0 μm. 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.1-0.4; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 85-115dB, and the shielding performance is enhanced.

[0116] Example 6

[0117] The difference from Example 1 is that the mesh size of the nickel powder is 500 mesh.

[0118] It can be seen from Examples 1 and 6 that as the nickel powder mesh number increases, the average pore size decreases to 20um, the porosity decreases to 55%; the gas permeability decreases to 7.0um 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.05-0.4; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 85-115dB, and the shielding performance is enhanced.

[0119] Example 7

[0120] The difference from Example 1 is that the drying tunnel temperature of the casting machine is always adjusted to 80°C.

[0121] It can be seen from Example 1 and Example 7 that after the drying tunnel temperature of the casting machine is fixed, the obtained green embryo will crack and curl, and the porous metal material cannot be formed.

[0122] Example 8

[0123] The difference from Example 1 is: 1 kg of waterborne polyurethane.

[0124] It can be seen from Examples 1 and 8 that the average pore size increases to 35um, the porosity decreases to 65%, and the gas permeability decreases to 6.0um. 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.2-0.7; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 70-100dB, and the shielding performance is weakened.

[0125] Example 9

[0126] The difference from Example 1 is: 50 g of hydroxymethyl cellulose.

[0127] It can be seen from Examples 1 and 9 that the increase of hydroxymethyl cellulose leads to an increase in the viscosity of the casting slurry, which is not conducive to the casting of the green embryo, and the green embryo becomes uneven, and the porous metal material cannot be formed.

[0128] Example 10

[0129] The difference from Example 1 is: spherical PS100g.

[0130] It can be seen from Examples 1 and 10 that the reduction of spherical PS reduces the average pore size of the porous metal material to 20um, the porosity to 45% and the gas permeability to 3.0um. 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.05-0.3; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 70-90dB, and the shielding performance is weakened.

[0131] Embodiment 11

[0132] The difference from Example 1 is: 150 g of spherical PS and 150 g of azobisisobutyronitrile.

[0133] It can be seen from Examples 1 and 11 that the use of spherical PS and azobisisobutyronitrile can reduce the average pore size of the porous metal material to 20um, the porosity to 65%; and the gas permeability to 2um. 2 ; In the frequency range of 1 to 4KHz, the sound absorption coefficient is 0.1-0.4; in the frequency range of 30MHz to 1.5GHz, the shielding performance is 85 to 115dB, and the shielding performance is significantly enhanced.

[0134] Example 12

[0135] The difference from Example 1 is that hydroxymethyl cellulose is not added.

[0136] It can be seen from Example 1 and Example 12 that without adding a thickener, the green embryo will be uneven, that is, the first sintering treatment will shrink unevenly during debonding, resulting in cracking, and the porous metal material cannot be formed.

[0137] Comparative Example 1

[0138] Traditional method for preparing porous nickel metal:

[0139] The traditional method for preparing porous nickel metal is as follows: polyurethane foam roughening → activation → chemical nickel plating → electroforming nickel → pyrolysis → heat treatment. A polyurethane soft foam with a thickness of 1 mm was selected as the matrix. 2 SO 4 +KMNO 4 The polyurethane foam was corroded to produce micro-scratches on the surface for roughening, and then the foam surface was activated with PdCl solution. The porous polyurethane was immersed in a mixed solution of nickel sulfate, sodium hypophosphite, sodium acetate and boric acid for 5 minutes to initially deposit a layer of nickel on the surface of the porous polyurethane. Then, the porous polyurethane with the initial nickel deposition was placed on a NiSO 4 7H 2 O 280g / L, NiCl·6H 2 040g / L, H 3 BO 3 In a plating solution with a pH value of 3.5 and a concentration of 40 g / L, the nickel-plated porous organic matter was obtained by electroplating at 50°C and a DC voltage of 9 V for 35 minutes.

[0140] The nickel-plated porous organic matter is loaded into a two-stage continuous kiln, first fired in the first stage continuous kiln (maximum temperature 500°C) in an air atmosphere for 6 hours to remove the polyurethane skeleton, then cooled and placed in the second stage continuous kiln (maximum temperature 1000°C) for sintering in a nitrogen-hydrogen mixture (15% hydrogen) for 12 hours, and then cooled and taken out of the kiln to obtain porous metallic nickel.

[0141] After testing, the porous metal nickel prepared by the traditional method has a thickness of 1mm, a density of 0.8g / cm3, an average pore size of 100um, a porosity of 95%, a gas permeability of 20mD, a sound absorption coefficient of 0.6-0.9 at a frequency of 1-4K Hz, and a shielding performance in the range of 80-110dB at a frequency range of 30MHz to 1.5GHz.

[0142] Compared with Example 1, Comparative Example 1 has a complex process and low efficiency. Many toxic and harmful reagents are used in the production process, and the thickness, pore size and porosity of the porous metal are greatly affected by the substrate. The currently known minimum thickness of mass-produced porous polyurethane is 1 mm. It is difficult to make the thickness of ultra-thin porous metal materials thin by traditional methods.

[0143] The test standards of the embodiments and comparative examples are as follows: the test standard for pore size is GB / T 38949-2020; the test standard for density is GB / T 17137-1997; the test standard for gas permeability is GB / T 15789; the test standard for sound absorption is GB / T 30142-2013; the test standard for shielding performance is GB / T 30142-2013GB / T 30142-2013.

[0144] pass Figure 1 and Figure 2 It can be seen that a porous metal material with uniform pore size distribution can be obtained through tape casting and two-stage sintering.

[0145] In summary, the present invention discloses a green and environmentally friendly method for preparing porous metal materials. Compared with traditional methods, the pore size, porosity and permeability of the porous metal materials can be adjusted by formula and sintering process. It is suitable for a variety of metal materials, and the thickness can be less than 1 mm, and the minimum is 0.05 mm.

[0146] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the invention without departing from the principles and purpose of the present invention. All such changes should fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a porous metal material, characterized in that: include: The metal powder, the binder, the pore-forming agent, the thickener and the water are mixed and stirred in a certain proportion to obtain a casting slurry; The casting slurry is introduced into a casting machine for casting and winding to obtain a metal composite film; The metal composite membrane is sintered in sequence to obtain a porous metal material.

2. The preparation method according to claim 1, characterized in that: In the process of obtaining the casting slurry, the content of the metal powder is 20wt% to 70wt%, the content of the binder is 5wt% to 20wt%, the content of the pore-forming agent is 5wt% to 20wt%, the content of the thickener is 0.1wt% to 2wt%, and the content of water is 10wt% to 40wt%.

3. The porous metal material according to claim 2, characterized in that: The binder includes at least one or more of waterborne polyurethane, waterborne epoxy resin, waterborne acrylic resin, waterborne silicone resin, waterborne acrylamide and polyvinyl alcohol.

4. The preparation method according to claim 2, characterized in that: The pore-forming agent includes at least one or more of carbon powder, ammonium bicarbonate, ammonium carbonate, urea, azodicarbonamide, azobisisobutyronitrile, 4,4-oxybisbenzenesulfonylhydrazide, p-toluenesulfonylhydrazide, spherical PS and spherical PMMA.

5. The preparation method according to any one of claim 2, characterized in that: The thickener includes at least one or more of lithium magnesium silicate, magnesium aluminum silicate, fumed SiO2, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

6. The preparation method according to any one of claims 1 to 5, characterized in that: During the process of the casting machine for casting and winding, the gap of the casting die head of the casting machine is 0.2-20 mm; the drying tunnel temperature of the casting machine is 40-100° C., which is set in a gradient sequence; the casting blast of the casting machine is 100-300 m 3 / h, the casting speed of the casting machine is 0.1m~1m / min, the casting base belt of the casting machine is a PET film, and the thickness of the PET film is 70~300um; the winding tension and unwinding tension of the casting machine are 100~600N respectively.

7. The preparation method according to any one of claim 6, characterized in that: The temperature of the drying tunnel increases first and then decreases.

8. The preparation method according to claim 7, characterized in that: The sintering process includes a first sintering process and a second sintering process performed sequentially, wherein the first sintering process includes: sintering in an air environment at a temperature of 300 to 500° C. for 1 to 24 hours; The second sintering treatment includes: sintering in a vacuum or argon or nitrogen or nitrogen-hydrogen mixed gas environment at a temperature of 600-1200° C. for 1-24 hours.

9. A porous metal material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.